Dimensions and perspectives of objectivist, constructivist, and postmodernist approaches on Malay food authenticity - Hasni, Muhamad Zulfikri; Ab Karim, Shahrim; Arshad, Mohd Mursyid; Abdullah, Haslinda; Mohd Sharif, Siti Nurhayati Khairatun (UiTM Press, 2020)
The authenticity of food can be a crucial area of studies in Malaysia context, especially Malay food. Although the idea of sustainability towards culture, heritage and tradition is always being discussed, the crucial part of what is authentic becomes vague and lessen. Past researchers have portrayed the understandings of authenticity based on three major dimensions of objectivist, constructivist and postmodernist approaches. Each approach is able to define “authenticity”. However, the understanding of the authenticity of Malay food is still needed to be underpinned theoretically and rigorously. As there is a lack of understanding towards clear dimensions of authenticity in Malay context, this raises an argument of which dimensions and approach are able to explain and highlight the true meaning and belief of Malay food reflected its core content of culture and heritage. Thus, this article intends to highlight the need for proclaiming and articulating the necessity of having a clear dimension of authenticity towards Malay food.